The pharmacokinetics and pharmacodynamics of denosumab in patients with advanced solid tumours and bone metastases: a systematic review. (September 2014) - Sohn, Winnie; Simiens, Mary Ann; Jaeger, Kelly; Hutton, Shauna; Jang, Graham
<x xml:space="preserve">Abstract</x> Aim The objective of this systematic review was to characterize the pharmacokinetics and pharmacodynamics of denosumab (XGEVA®), a fully human IgG2 monoclonal antibody which binds to receptor activator of nuclear factor kappa‐B ligand (RANKL), for the treatment of skeletal‐related events (SREs) in patients with advanced cancer and bone metastases. Methods A total of 708 patients (116 healthy patients and 592 patients with solid tumours or multiple myeloma and bone metastases) included in seven clinical studies were evaluated for denosumab pharmacokinetics. Denosumab was administered as a single subcutaneous (s.c.) dose or multiple s.c. doses, ranging from 0.1 to 3.0 mg kg−1 or 30 mg to 180 mg fixed dosing, every 1 or 3 months for up to 45 months. Results Consistent with the results in healthy adults, single s.c. doses of denosumab demonstrated dose‐dependent, non‐linear pharmacokinetics in advanced cancer patients with bone metastases across a wide dose range (0.1–3.0 mg kg−1). Reductions in levels of the bone turnover marker, uNTx/Cr, were observed within 1 day. The duration of reductions generally increased with dose and dosing frequency. In patients with solid tumours and bone metastases, pharmacokinetics and pharmacodynamic comparisons across tumour types and concomitant cancer therapies (chemotherapies and/or hormone therapies) suggest that neither tumour type nor type of concomitant therapy markedly affects denosumab pharmacokinetics or pharmacodynamics. Conclusions Denosumab displayed non‐linear pharmacokinetics at doses below 60 mg but at higher doses, denosumab exposure increased approximately dose‐proportionally in advanced cancer patients with bone metastases. Following a 120 mg, every 4 weeks dosing schedule, similar denosumab pharmacokinetics and pharmacodynamics were observed across tumour types and were independent of concomitant cancer therapies.